A New Plastic Design Approach for the Vertical-Side-Plating Thickness of Ice-Strengthened Ships Suffering from Ice Floe Impacts - Mengying Mu; Kailing Guo; Wei Cai; Ling Zhu; Zhenyu Pi; Shuo Zhou (Journal of Marine Science and Engineering, 2024)
Ice-strengthened ships inevitably suffer from ice floe impacts during navigation in icy regions. Under some extreme-ice-impact loadings, the ship structure will experience plastic deformations. The magnitude of plastic deformation is highly correlated with the ice floe-impact energy level. During most ice impacts, only the ship’s plate undergoes minor plastic deformation. Considering that the structure still has a high structural strength with a minor permanent deformation, developing a structural plastic design method for polar ships has become a hot research issue in current studies. Therefore, in this paper, based on the rigid-plastic theory and the ice-crushing-energy approach, an experimentally verified theoretical model for predicting plastic deformations of the vertical-side plate of polar ship subjected to ice floe impacts was established. According to the analytical solutions of the plastic deformation, the plastic design formula to determine the plating thickness of ice-strengthened ships subjected to ice floe impacts was further derived based on the plastic design criteria. In addition, the parameter analysis of ice strength described by the ice pressure–area relationship, allowable-permanent-set parameter, impact energy and ice shape were conducted, and plating-thickness design curves with different design parameters were given. The design of plating thickness is very sensitive to the determinations of the allowable-permanent set and ice pressure–area curves. The designed plating thickness decreased with the increase of the allowable-permanent set. Moreover, a comparative analysis of the designed plating thickness for ice floe impact and rigid-mass impact was also carried out. Under the same impact conditions, due to energy absorption caused by ice damage, the designed thickness of the plate for rigid-mass impact was much larger than that for the ice impact. It is necessary to consider the impact-induced ice damage and energy dissipation in a structural design, instead of using rigid impact loads for conservative design. The research in this paper can provide some useful references for the structural design of ice-strengthened ships subject to ice floe impacts.